Analysis of ionospheric and geomagnetic fields changes in Thailand during the May 2024 geomagnetic storm - Myint, Lin M.M.; Perwitasari, Septi; Nishioka, Michi; Saito, Susumu; Kaewthongrach, Rungnapa; Supnithi, Pornchai (My University, 2025)
The extreme geomagnetic storm of May 2024, the most severe in two decades of space weather history up to date, had widespread effects on the ionosphere, from the polar regions to the magnetic equator. This study examines the responses of the equatorial ionosphere and geomagnetic field over Thailand during this geomagnetic storm, utilizing data from GNSS receivers, magnetometers, and ionosondes near the magnetic equator and low-latitude regions of Thailand. We analyze the direct and indirect impacts of interplanetary magnetic field (IMF) and interplanetary electric field (IEF) variations, driven by solar storms, on local equatorial magnetic fields and ionospheric parameters. Our finding reveals that storm-driven electric fields, particularly prompt penetration electric fields (PPEF) and disturbance dynamo electric fields (DDEF), strongly influenced equatorial electric field (EEF), causing notable fluctuations in total electron content (TEC), critical frequency of F2 (foF2), and virtual height of F layer (h’F). The Pearson correlation analysis highlights the rapid coupling between interplanetary magnetic field (IMF) and local equatorial magnetic fields during geomagnetic storms. These observations enhance our understanding of geomagnetic storm impacts in equatorial regions, which is crucial for improving space weather forecasting and mitigation strategies, especially for GNSS-dependent systems and radio communications.
Keywords: Equatorial ionization anomaly; Equatorial ionospheric irregularity; Geomagnetic field; Geomagnetic storm; Ionosphere; Solar storm